Examining the Effectiveness of Legal Empowerment as a Pathway Out of Poverty : A Case Study of BRAC - Kolisetty, Akhila (World Bank, Washington, DC, 2014)
This paper examines the current status of justice and dispute-resolution mechanisms in Bangladesh, ranging from the formal justice system to the traditional shalish (a form of dispute resolution), and focuses on the costs and benefits of utilizing nongovernmental organization (NGO)-led legal services programs as an alternative form of justice delivery and dispute resolution for the poor, with a focus on women and girls. In particular, this paper takes a closer look at a the Human Rights and Legal Aid Services (HRLS) program of BRAC, a leading NGO that works to empower the poorest and most vulnerable in Bangladesh and eleven other countries across the world. HRLS provides a combination of Bangladesh Rural Advancement Committee (BRAC)-led shalish, human rights community based education, community mobilization through a corps of community-based outreach workers (known as shebikas), and recourse to the courts via a network of panel lawyers if needed. This paper will examine the successes of this model in rural Bangladesh as well as the challenges it faces in making an impact on solving the justice problems of the poor and contributing to gender equity. Ultimately, it aims to present a case study that illustrates the strengths and challenges of a legal empowerment model that is quickly gaining traction around the world.